Seychelles : 2008 Article IV Consultation and Request for a Stand-By Arrangement; Staff Report; Staff Supplement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Seychelles. (IMF Staff Country Reports; Country Report, 2008)
This paper presents Seychelles' 2008 Article IV Consultation and Request for a Stand-By Arrangement. Large macroeconomic imbalances and vulnerabilities resulting from longstanding unsustainable macroeconomic policies, combined with recent external shocks, culminated in mid-2008 with the near-exhaustion of foreign reserves and missed payments on public debt obligations. Growth is declining, and inflation has risen sharply. The pegged exchange rate that was incompatible with fundamentals, together with a complex system of exchange restrictions and controls, has resulted in economic dislocation, a parallel exchange market, and pervasive dollarization.